Evaluasi Program Kesehatan Public Safety Center (PSC) 119 Dinas Kesehatan Kabupaten Cianjur - Laili, Ayu; Dwi Pratiwi , Fujiyanti; Imelda Sari, Mega; Ghiska Putri, Dhea (JURNAL KESEHATAN KARTIKA, 2023)
ABSTRACT Public safety center is a service center for ensure people which is related to Emergency needs at each district/city to gain fast, proper, and accurate respons. PSC 119 is ruin for 24 hours continously and collaborate with related unit. This research/study using qualitative methods by cases study design methods. Research instrument using interview guidelines. This research focus point is PSC 119 Program Evaluation at Cianjur District Public Health Office. Evaluation methods using CIPP (Contect, Input, Process, Product). The result of evaluation input facilities is 1 Car Ambulance and 2 Motorcycle Ambulance. Car Ambulance is not fulfilled Emergency standar yet. The Obsctacle in program implementation is lacked of knowledge of Nurse about Emergency Implementation because the part of Paramedics doesn’t have Basic Trauma and Cardiac Life Support (BTCLS) certification, announcing about PSC 119 the to the other people, and not being collaborated with another sector. Summary is there are several reccomendation for Dinas Kesehatan Kabupaten Cianjur/Cianjur District Public Health Office PSC 119 team for implementating the programm. that is: Basic Trauma Cardiac Life Support (BTCLS) training for all Pramedic members at Dinas Kesehatan Kabupaten Cianjur/Cianjur District Public Health Office, Generalized the Ambulance Standart and addition for Ambulance PSC 119, Dinas Kesehatan Kabupaten Cianjur/Cianjur District Public Health Office have to collaborated with others sector which is Police, Fire station, Disaster Management Agency (BPBD), and related sector. And the last, announcing the PSC 119 Programm to general public. Keyword: PSC 119, SPGDT, Emergency